# Algebra II

posted by Jon

Assume that no denomenator equals 0.

(7x^2+3x-9)-(-x^2+8x-3)

= 7x^2+3x-9+x^2-8x+3
= (7x^2+x^2)+(3x-8x)+(-9+3)
= 8x^2+-5x+-6

1. Dan

What exactly is your question? I don't even see a denominator anywhere :)

What you have is right so far. If you want to finish that question you need to use the quadratic formula

x = (-b +/- square root(b^2 - 4ac)) / 2a

x = (5 +/- square root (25 + 192)) / 16

x = (5 +/- square root (217)) / 16

which yields x1 = 1.23 and x2 = -0.61

2. Jon

(7x^2+3x-9)-(-x^2+8x-3) is the question. the rest is my work

3. Dan

Your solution is perfect, did you just want confirmation?

4. Jon

yes

## Similar Questions

1. ### Pre-Algebra

If negative 20 equals 168, negative 15 equals 153, negative 10 equals 138, negative 5 equals 123, 0 equals 108, 5 equals 93, 10 equals 78, 15 equals 63, 20 equals 48, then what is the rule?
2. ### Pre-Algebra

If negative 20 equals 168, negative 15 equals 153, negative 10 equals 138, negative 5 equals 123, 0 equals 108, 5 equals 93, 10 equals 78, 15 equals 63, 20 equals 48, then what is the rule?
3. ### Algebra II (check)

Assume that no denominator equals 0. 5x^3(7x)^2 = 5*7*7+x^3+x^2 = 245x^5(answer)
4. ### Algebra II (check)

Assume that no denominator equals 0. (2x-3)^2 = 2x * 2x -3 * -3 = 4x-9(answer)
5. ### Algebra II (check)

Assume that no denominator equals 0. sqrt 16x^2y^4 = sqrt (4x)y^2 = 4xy^2(answer)
6. ### Algebra II (check)

Assume that no denominator equals 0. 2+i/1-3i = 2+i/1-3i = (2+i/1-3i) * (1+3i/1+3i) = (2+3i^2)/(1-9i^2) = (2/1) - (1/3i) = 2-1/3i(answer)
7. ### algebra ll

solve the system of equation. 4x - 3y equals 14 y equals -3x plus 4 and another following up 4x - 3 equals 8 2x plus 5y equals 9 thatnk u for the help
8. ### algebra ll

if f(x)equals 5x^2 minus 4/x, find f(4) my ans. is f(4) equals 66 if wrong answer and show work please
9. ### algebra

Could someone show me how to solve this joint variation problems?
10. ### Math

Hi ya! So I got a question like when I'm rationalzing a denomenator in order to get simple radical form I really don't know what to do for example this problem (6^(2^-1)-3^(2^-1))^-1 ok so I know your trying to get it so it's a perfect …

More Similar Questions